2011
DOI: 10.1162/jocn.2010.21475
|View full text |Cite
|
Sign up to set email alerts
|

Life Span Differences in Electrophysiological Correlates of Monitoring Gains and Losses during Probabilistic Reinforcement Learning

Abstract: Abstract■ By recording the feedback-related negativity (FRN) in response to gains and losses, we investigated the contribution of outcome monitoring mechanisms to age-associated differences in probabilistic reinforcement learning. Specifically, we assessed the difference of the monitoring reactions to gains and losses to investigate the monitoring of outcomes according to task-specific goals across the life span. The FRN and the behavioral indicators of learning were measured in a sample of 44 children, 45 ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
208
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(255 citation statements)
references
References 88 publications
42
208
3
Order By: Relevance
“…From this perspective, our finding that symptoms of DMDD were prospectively associated with an enhanced RewP in response to monetary reward is inconsistent with evidence suggesting that chronic irritability is associated with impaired reward learning (Adleman et al, 2011). However, there is emerging evidence in both adults (Cavanagh 2015) and children (Hämmerer et al 2010) to suggest that the RewP is specific to surprising rewarding events and may not be directly associated with behavioral adjustments. Rather, the RewP may encode and classify whether an outcome is beneficial to a predefined goal (Hämmerer et al 2010).…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…From this perspective, our finding that symptoms of DMDD were prospectively associated with an enhanced RewP in response to monetary reward is inconsistent with evidence suggesting that chronic irritability is associated with impaired reward learning (Adleman et al, 2011). However, there is emerging evidence in both adults (Cavanagh 2015) and children (Hämmerer et al 2010) to suggest that the RewP is specific to surprising rewarding events and may not be directly associated with behavioral adjustments. Rather, the RewP may encode and classify whether an outcome is beneficial to a predefined goal (Hämmerer et al 2010).…”
contrasting
confidence: 73%
“…However, there is emerging evidence in both adults (Cavanagh 2015) and children (Hämmerer et al 2010) to suggest that the RewP is specific to surprising rewarding events and may not be directly associated with behavioral adjustments. Rather, the RewP may encode and classify whether an outcome is beneficial to a predefined goal (Hämmerer et al 2010). Speculatively, children with early emerging symptoms of DMDD may be hypersensitive to reward and that hypersensitivity may lead to exaggerated stimulusresponse learning, such that they create strong associations between a particular pattern of responses or thinking and rewarding environmental cues.…”
mentioning
confidence: 99%
“…In contrast, other studies have reported reduced neural activity and learning in aged subjects' response to rewards, indicating potential reductions in reward sensitivity Hammerer et al, 2011). Consistent with these latter findings as well as the findings in the present study, a recent paper by Maasberg et al (2011) found a reduction in reward anticipation in aged rats performing a sucrose preference task.…”
Section: Frontiers In Neuroscience | Decision Neurosciencesupporting
confidence: 91%
“…Previous studies focusing on the age-related alterations in feedback evaluation processes found both differences and similarities in the morphology of the FRN and related P3 between young and elderly participants [35,36,39,[56][57][58][59][60]. The finding of the present study that the magnitude of the FRN component for the negative feedback (the balloon burst itself) did not differ between the two age groups suggests that the rapid processing of negative feedback valence was equally functional in both groups emphasizing the intact sensitivity to negative events in the elderly.…”
Section: Interpretation Of the Electrophysiological Resultsmentioning
confidence: 97%